2014
DOI: 10.1097/01.mib.0000437499.52922.b1
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Evidence for Central Nervous System Plasticity in Animal Models of Inflammatory-mediated Gastrointestinal Pain

Abstract: The included studies provide strong evidence for CNS plasticity following GIT inflammation, specifically in the spinal cord dorsal horn. This evidence includes altered visceromotor responses and indices of referred pain, elevated neural activation and peptide content, and increased neuronal excitability. This evidence supports continued use of this approach for preclinical studies; however, there is substantial scope to improve study design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 156 publications
(365 reference statements)
2
17
0
1
Order By: Relevance
“…Our findings regarding the study quality of animal studies are in agreement with other animal systematic reviews which also reported lack of randomization, blinding, insufficient evidence of random housing of the animals and inappropriate statistical analysis, which are the major factors causing bias and false positive results .…”
Section: Discussionsupporting
confidence: 90%
“…Our findings regarding the study quality of animal studies are in agreement with other animal systematic reviews which also reported lack of randomization, blinding, insufficient evidence of random housing of the animals and inappropriate statistical analysis, which are the major factors causing bias and false positive results .…”
Section: Discussionsupporting
confidence: 90%
“…In order to verify the quality of the clinical study, the ‘Clinical Studies Bias Risk' was used following the protocol used by Cochrane with adaptations, and for the preclinical studies, the models suggested by Araújo‐Filho et al . and Farrell et al . were used.…”
Section: Methodsmentioning
confidence: 99%
“…Based on what we know about pain processing circuits, this suggests the source of chronic and referred pain lies within the central nervous system (CNS). These clinical observations are supported by work in animal models of visceral inflammation that have provided behavioral, anatomical, molecular, and physiological evidence to implicate spinal circuits in the development of altered pain responses in IBD (Farrell et al, 2014). In spite of this evidence, little is known about the precise mechanisms of chronic pain development and maintenance in IBD.…”
mentioning
confidence: 87%
“…Evidence that the CNS is involved in the processing of inflammation-induced visceral pain has been demonstrated in animal models at behavioral, anatomical, molecular, and physiological levels of analysis (Farrell et al, 2014). Briefly, it has been shown that animals develop referred hypersensitivity of the hind paw and abdomen following colitis (Lamb et al, 2006), and that this sensitivity remains after the resolution of inflammation (Eijkelkamp et al, 2009).…”
Section: Altered Nervous System Signaling In Ibd-related Painmentioning
confidence: 99%
See 1 more Smart Citation